Understanding feline idiopathic cystitis. Issue 3 (6th April 2018) - Sparkes, Andrew
Abstract : Feline idiopathic cystitis is a common disease of unknown aetiology. Despite numerous studies, our understanding of this disease remains poor and although there are some interesting and attractive theories about the pathogenesis of the disease, much remains to be confirmed. Along with our poor understanding of the pathogenesis of disease, knowledge of effective therapeutic intervention is also rudimentary. This article explores the current state of knowledge of these aspects of the disease and takes an evidence‐based approach to managing feline idiopathic cystitis.